Vaccine-associated paralytic poliomyelitis in India during 1999: decreased risk despite massive use of oral polio vaccine - Kohler Kathryn A.; Banerjee Kaushik; Gary Hlady W.; Andrus Jon K.; Sutter Roland W. (The World Health Organization, 2002)
OBJECTIVE: Vaccine-associated paralytic poliomyelitis (VAPP) is a rare but serious consequence of the administration of oral polio vaccine (OPV). Intensified OPV administration has reduced wild poliovirus transmission in India but VAPP is becoming a matter of concern. METHODS: We analysed acute flaccid paralysis (AFP) surveillance data in order to estimate the VAPP risk in this country. VAPP was defined as occurring in AFP cases with onset of paralysis in 1999, residual weakness 60 days after onset, and isolation of vaccine-related poliovirus. Recipient VAPP cases were a subset with onset of paralysis between 4 and 40 days after receipt of OPV. FINDINGS: A total of 181 AFP cases met the case definition. The following estimates of VAPP risk were made: overall risk, 1 case per 4.1 to 4.6 million OPV doses administered; recipient risk,1 case per 12.2 million; first-dose recipient risk, 1case per 2.8 million; and subsequent-dose recipient risk, 1 case per 13.9 million. CONCLUSION: On the basis of data from a highly sensitive surveillance system the estimated VAPP risk in India is evidently lower than that in other countries, notwithstanding the administration of multiple OPV doses to children in mass immunization campaigns.